Kontribusi Kepemimpinan Pelayan Kepala Sekolah, Motivasi Kerja dan Kelengkapan Sarana dan Prasarana Terhadap Kinerja Guru - N. Nilon; I.N. Natajaya; I.G.K.A Sunu (Pascasarjana Universitas Pendidikan Ganesha, 2021)
This study was conducted to identify the contribution between the principal servant leadership variables, work motivation, and facilities' completeness and facilities to teacher performance. This research is categorized as ex-post-facto using multiple linear regression analysis. The sample in this study was selected with a saturated sample technique so that the number of research samples was the same as the population, namely, 86 teachers. Data collection was carried out using a questionnaire from principal servant leadership, work motivation and completeness of facilities and teacher performance. The study findings confirm that (1) there is a contribution of principal servant leadership to teacher performance by 7.4% 2) there is a contribution of work motivation to teacher performance by 28.55%; 3) there is a contribution of the completeness of facilities and infrastructure to teacher performance by 14.64%; and 4) there is a simultaneous contribution between the principal servant leadership, teacher work motivation, and completeness of facilities and infrastructure to teacher performance by 50.6%.